2016
DOI: 10.5588/ijtld.15.0864
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <I>kat</I>G and <I>inh</I>A mutations to guide isoniazid and ethionamide use for drug-resistant tuberculosis

Abstract: SUMMARY BACKGROUND Depending on the presence of mutations that determine isoniazid (INH) susceptibility (katG and inhA), Mycobacterium tuberculosis may be susceptible to high doses of INH or ethionamide (ETH). OBJECTIVE To describe the INH resistance profile and association of katG mutation with previous INH treatment and level of drug resistance based on rapid molecular drug susceptibility testing (DST) in southern Brazil and central Mozambique. DESIGN Descriptive study of 311 isolates from Ribeirão Pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 29 publications
3
59
1
12
Order By: Relevance
“…However, this finding did not represent a statistically significant difference. [38] This subject remains unanswered by our study and could be an area for further research.…”
Section: Researchmentioning
confidence: 87%
See 1 more Smart Citation
“…However, this finding did not represent a statistically significant difference. [38] This subject remains unanswered by our study and could be an area for further research.…”
Section: Researchmentioning
confidence: 87%
“…[37] Our study did not investigate the relationship between INH resistance-conferring mutations and history of prior use of INH. Bollela et al [38] reported a direct link between prior INH exposure for latent or active TB and predominance of katG mutations. They found that a katG mutation was more frequent among isolates from patients with a history of INH use than in those with no INH exposure (68.8% v. 31.2%).…”
Section: Researchmentioning
confidence: 99%
“…As with rpo B gene, the frequency of kat G mutations and inh A mutations has been seen to vary geographically; a higher prevalence of kat G mutations in Mozambique have been noted compared with Brazil where mutations in inh A promoters is more commonly associated with isoniazid resistance (Bollela et al . ). This suggests a diversifying spectrum of mutational patterns involved in MDR.…”
Section: Resultsmentioning
confidence: 97%
“…Las mutaciones en los genes de Mycobacterium tuberculosis katG e inhA, han sido reportados como los responsables del 60 -80% de los aislados resistentes a isoniacida [27][28][29][30] .…”
Section: Discussionunclassified